Implementing Fuzzy Sets and Processing Fuzzy Logic Information by Molecules - Pier Luigi Gentili (Proceedings, 2022)
Fuzzy logic models human capacity to make decisions using natural language, and it is widely used in the field of Artificial Intelligence. This contribution supports the hypothesis that the effectiveness of fuzzy logic in mimicking human capability to compute with words is due to the structural and functional analogies between the human nervous system and fuzzy logic systems. Furthermore, this work demonstrates that fuzzy logic can be processed by molecules and chemical reactions in wetware beyond the traditional methods based on electronic circuits and software. This innovative way of processing fuzzy logic allows the development of Chemical Artificial Intelligence and the design of new computational machines, more similar to the brain rather than electronic computers, both in composition and performance.